Development of Live Action Audiovisual Regarding The Consumption of Taking Anti-Diabetic Drugs In Diabetic Patients - Rafi, Dzaky Abdur; Sudiyat, Rahmat (Eduvest - Journal of Universal Studies, 2025)
Bandung found an increase in the number of DM patients in 2020-2022 (43,906 to 44,329) (Jabar, 2022). It often happens that many patients are saturated and not compliant with treatment, increasing the risk of complications and requiring media in overcoming DM. Based on the inspection of media needs at the Diabetes Wound Care Specialist Hospital through the Central Coordinator, the Head Nurse of the Buahbatu branch and the Head Nurse of the Baleendah branch said that the age of active patients was 40-70 years and it was still found that they were not diligent in taking medication and wanted media impressions that were taken home, reviewed and watched again. So that the media that is suitable for use is Audiovisual Live Action regarding Anti-diabetes Medication Consumption. Method: Research and Development with ADDIE development model, Place: RUMAT Bandung, Time: March 5-June 31, 2024 and Target: DM patients of RUMAT Bandung. Results: Media needs analysis requires Live Action Audiovisual, Design includes Pre-Production, Production and Post-Production, Media development is declared "Very feasible" by material and media experts, Implementation of large group tests with "Very feasible" criteria, Evaluation of Gform 65 Respondents and Youtube 439 likes and 559 views. Conclusion: Live Action Audiovisual Media is said to be very feasible with a percentage of 94%.